HUBUNGAN PERSEPSI SISWA TENTANG KOMPETENSI PEDAGOGIK DAN KOMPETENSI PROFESIONAL HASIL BELAJAR SISWA - Fitri Nuryani; Sumadi Sumadi; Sudarmi Sudarmi (JPG (Jurnal Penelitian Geografi), 2016)
This study ained to determine and analyze (1) the relations between student perception of pedagogic competence teacher with learning social outcomes (2) the relations between student perception of professional competence teacher with learning social outcomes (3) the relations between student perception of pedagogic competence and professional competence teacher with learning social outcomes. The method was correlasional. Based on the analysis of the data it obtained the following results, (1) there was a significant positive relationship between the perception of students on pedagogical competence of teachers to student learning outcomes (2) there was a significant positive correlation between the students' perceptions about the professional competence of teachers to student learning outcomes (3) there was a positive relationship between the perception of students on pedagogical competence of teachers and professional competence of teachers to student learning outcomes. Penelitian ini bertujuan untuk mengetahui dan menganalisis (1) hubungan antara persepsi siswa tentang kompetensi pedagogik guru IPS dengan hasil belajar siswa (2) hubungan antara persepsi siswa tentang kompetensi profesional guru IPS dengan hasil belajar siswa (3) hubungan antara persepsi siswa tentang kompetensi pedagogik dan kompetensi profesional guru IPS secara bersamaan dengan hasil belajar siswa.Metode yang digunakan adalah metode korelasional.Berdasarkan analisa data diperoleh hasil yaitu (1) ada hubungan positif yang signifikan antara antara persepsi siswa tentang kompetensi pedagogik guru dengan hasil belajar siswa (2) ada hubungan positif yang signifikan antara antara persepsi siswa tentang kompetensi profesional guru dengan hasil belajar siswa (3)ada hubungan positif antara antara persepsi siswa tentang kompetensi pedagogik guru dan kompetensi profesional guru dengan hasil belajar siswa.Kata kunci : kompetensi pedagogik, profesional, hasil belajar